Clinical features of the DOK7 neuromuscular junction synaptopathy. - Palace, J; Lashley, D; Newsom-Davis, J; Cossins, J; Maxwell, S; Kennett, R; Jayawant, S; Yamanashi, Y; Beeson, D (2007)
Mutations in DOK7 have recently been shown to underlie a recessive congenital myasthenic syndrome (CMS) associated with small simplified neuromuscular junctions ('synaptopathy') but normal acetylcholine receptor and acetylcholinesterase function. We identified DOK7 mutations in 27 patients from 24 kinships. Mutation 1124_1127dupTGCC was common, present in 20 out of 24 kinships. All patients were found to have at least one allele with a frameshift mutation in DOK7 exon 7, suggesting that loss of function(s) associated with the C-terminal region of Dok-7 underlies this disorder. In 15 patients, we were able to study the clinical features in detail. Clinical onset was usually characterized by difficulty in walking developing after normal motor milestones. Proximal muscles were usually more affected than distal, leading to a 'limb-girdle' pattern of weakness; although ptosis was often present from an early age, eye movements were rarely involved. Patients did not show long-term benefit from anticholinesterase medication and sometimes worsened, and where tried responded to ephedrine. The phenotype can be distinguished from 'limb-girdle' myasthenia associated with tubular aggregates, where DOK7 mutations were not detected and patients respond to anticholinesterase treatments. CMS due to DOK7 mutations are common within our UK cohort and is likely to be under-diagnosed; recognition of the phenotype will help clinical diagnosis, targeted genetic screening and appropriate management.